2011
DOI: 10.1167/iovs.10-6648
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Perimacular Inner Retinal Layer Thickness in Normal Eyes Measured by Fourier-Domain Optical Coherence Tomography

Abstract: Inner retinal layer thickness, as measured by FD-OCT, varies significantly with age and axial length. The effect is small but clinically relevant in the interpretation of inner retinal layer thickness measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
49
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 30 publications
11
49
8
Order By: Relevance
“…They found that GCC thickness significantly decreases with age [23]. This result is consistent with the previously published histological findings on human retina that demonstrate a decrease in the density of photoreceptors, retinal ganglion cells and retinal pigment epithelial cells with increasing age [39].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…They found that GCC thickness significantly decreases with age [23]. This result is consistent with the previously published histological findings on human retina that demonstrate a decrease in the density of photoreceptors, retinal ganglion cells and retinal pigment epithelial cells with increasing age [39].…”
Section: Discussionsupporting
confidence: 90%
“…Using the RTVue-100 OCT Kim et al [23] examined 182 healthy subjects with ages ranging between 22 and 84 years. They found that GCC thickness significantly decreases with age [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[12][13][14] The GCC thickness obtained from the unaffected fellow eyes was 94.7 ± 5.4 mm, which is comparable to that in other studies. The postoperative GCC thickness in our study was 84.2 ± 10.8 mm at 6 months, and it was thinner than normal GCC thickness by approximately 10 mm.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, in our study the peripapillary RNFL and macular GCC thicknesses were measured by SD OCT to detect early neuronal degeneration. It is well known that RNFL and GCC thicknesses decreased with age [18,19]. As shown in Table 1, there was no significant difference with respect to age between diabetic and normal subjects.…”
Section: Discussionmentioning
confidence: 76%